Attributions of Responsibility for Terrorist Attacks: The Role of Group Membership and Identification - Doosje, Bertjan; Zebel, Sven; Scheermeijer, Marieke; Mathyi, Pauline (International Journal of Conflict and Violence (IJCV), 2007)
Three studies examine how people’s attributions of responsibility for terrorist attacks depend on their group membership and their identification with the victim (study 1) or their identification with the victim’s or perpetrator’s ingroup (studies 2 and 3). We observe that people’s group membership (perpetrator group versus victim group) determines the judgments of responsibility for recent terrorist attacks. Members of the perpetrator group hold the direct perpetra- tors responsible, while members of the victim group perceive the perpetrator world as a whole as relatively responsible as well. Identification with the victim (study 1) or victim group (studies 2 and 3) strengthens attributions of responsibility to the whole perpetrator group, and this relationship is partially mediated by the perceived typicality of the perpetrator for the whole group. We discuss possible explanations for this pattern, and indicate the implications of these results in terms of improving intergroup relations.